2011
DOI: 10.1007/s00415-011-6179-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary pituitary lymphoma in an immunocompetent patient: a rare clinical entity

Abstract: Primary pituitary lymphoma in immunocompetent patients is an exceedingly rare clinical entity. We report the case of a 41-year-old woman with initial polydipsia and polyuria. When laboratory evaluation revealed panhypopituitarism, a pituitary enhanced MRI was performed and was suggestive of a pituitary adenoma. Obstructive hydrocephalus provoked by enlarged sellar mass was also demonstrated during observation, and a shunt procedure following lesion resection was carried out. Histopathological examination and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…We also identified that gene mutation of TP53 and BCL6 was responsible for prognostic difference. Normally, the treatment of PPL often follows the management protocol of PCNSL consisting of surgery, chemotherapy and/or radiotherapy ( 6 ). However, it is said that surgical intervention suggests no obvious benefits in the outcome of PCNSL and the neurotoxic effects of radiotherapy should be noted ( 3 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified that gene mutation of TP53 and BCL6 was responsible for prognostic difference. Normally, the treatment of PPL often follows the management protocol of PCNSL consisting of surgery, chemotherapy and/or radiotherapy ( 6 ). However, it is said that surgical intervention suggests no obvious benefits in the outcome of PCNSL and the neurotoxic effects of radiotherapy should be noted ( 3 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether BCL6 can be considered as a prognostic factor of PCNSL is still controversial. Cady et al investigated that BCL6 was associated with inferior OS alone or concomitant with del ( 6 ) (q22) ( 18 ). However, the expression of BCL6 was paradoxically correlated with the prognosis of PCNSL.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine dysfunction appears to occur in roughly 50% of the studies reviewed in this study. 4,5,8,11,15–17,19,21,23,24,29 Studies of non-functioning pituitary macroadenomas suggest that pituitary dysfunction is present in more than 30% 30 which would correlate well with lymphomas. By far the most common lymphoma subtype reported was B-cell (65%), the other cases were made up of mixed cell, T-cell, Burkitt cell and mucosa-associated lymphoid tissue cell types.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The majority of cases are associated with congenital and acquired immunodeficiency, whereas around 29 case reports with sellar and suprasellar location concern immunocompetent patients, like ours. 4,5,13 Regarding radiologic evaluation, there are no distinct radiological features of sellar and suprassellar lymphomas that can aid the differential diagnosis. On MRI, they usually appear as iso-or hypointense on T1 and T2-weighted images and tend to have homogeneous enhancement following radio-contrast administration.…”
Section: Discussionmentioning
confidence: 99%